2011
DOI: 10.1111/j.1439-0531.2010.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leptin Level in Hyperlipidemic Mares and Their Newborn Foals

Abstract: The aim of this study was to evaluate the relationship between plasma leptin and lipid levels in breeding mares and their newborn foals. The study was conducted on 17 Polish cold-blood mares and their newborn foals. The mares were divided into two groups, according to the course of delivery. These groups were seven mares which had a normal delivery and 10 mares which had required veterinary intervention during their delivery. Blood samples were taken from the jugular vein of both the mares and their foals. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
3
0
1
Order By: Relevance
“…In line with the absence of differences in growth and thyroid hormones, there were also no differences in plasma leptin nor adiponectin concentrations between groups. In agreement with these observations, foals born to hyperleptinemic mares did not have elevated plasma leptin concentration from birth until 4 days of age [ 96 ]. These observations do not exclude a transient elevation of plasma leptin concentrations.…”
Section: Discussionsupporting
confidence: 60%
“…In line with the absence of differences in growth and thyroid hormones, there were also no differences in plasma leptin nor adiponectin concentrations between groups. In agreement with these observations, foals born to hyperleptinemic mares did not have elevated plasma leptin concentration from birth until 4 days of age [ 96 ]. These observations do not exclude a transient elevation of plasma leptin concentrations.…”
Section: Discussionsupporting
confidence: 60%
“…Some reports indicate that high plasma leptin concentration exists together with elevated plasma lipids content (Frank et al, 2006;Kędzierski et al, 2011;Pleasant et al, 2013). This is the reason for the analysis of changes in plasma leptin in relation to TG, glycerol and FFA concentrations in this study; however, no important relationship was found.…”
Section: Discussionmentioning
confidence: 51%
“…However, as previously reported (Watson et al 1990), within our donkey population TGs were also positively correlated with BCS. It is interesting to note that the correlation between TGs and BCS is not clear in horses (Kedzierski and Kapica 2008;Kedzierski et al 2010). …”
Section: Discussionmentioning
confidence: 98%